Pesca artesanal no município de São João de Pirabas: um olhar sobre as oportunidades e desafios, ao longo dos anos - BARROSO, Dariane Pinheiro (2025)
The small scales artisanal fishing employs around 90% of fishermen worldwide. The state of Pará has 562 km of coastline and has around about 163 communities that practice artisanal fishing, distributed across 17 municipalities. In this context, this study has the objective of characterize the community of artisanal fishermen located in Pirabas, taking into consideration their main cultural and historical characteristics. The primary data collection for analysis was done through a participatory questionnaire and through multivariate bibliographic sources. The data analyzed indicated that the actors who work in artisanal fishing in the municipality of São João de Pirabas have mussels, fish and crustaceans as their merchandise, in addition to their subproducts, for example, the isinglass and even with a wide variety of merchandise, this group still obtains discreet financial income, a fact that lead many professionals in this area to situations of marginalization or oblivion. Considering that challenging panorama, the urgency of strategic action to promote improvements in the working conditions of these actor become evident. It is necessary to take measures such as the establishment of policies that ensure fair remuneration, the implementation of professional training programs and the creation of mechanisms for efficient fundraising by public authorities, wich are crucial to ensuring the sustainability of the activity.